Granulocyte Colony-Stimulating Factor Combined With Transcutaneous Electrical Acupoint Stimulation in Treatment of Unresponsive Thin Endometrium in Frozen Embryo Transfer Cycles - Song, Linjiang; Zhang, Qinxiu; Zhu, Shaomi; Shan, Xudong (Frontiers in Reproductive Health, 2021)
Objective: This trial was designed to assess the treatment effects of granulocyte colony-stimulating factor (G-CSF) and transcutaneous electrical acupoint stimulation (TEAS) on thin endometrium in frozen-thawed embryo transfer (FET) cycles. Methods: 99 patients with previous cancellations of embryo transfer were included, 56 of whom were prospectively treated with intrauterine perfusion of G-CSF in subsequent FET cycles. The selected patients were randomized into the G-CSF perfusion only group and G-CSF perfusion combined with TEAS group. The other 43 patients were retrospectively included as controls. Results: Compared to previous cycles, endometrial thickness statistically significantly increased in the two treatment groups (5.97±0.60 &7.52±0.56 and 6.14±0.52 & 7.66±0.44; P =0.00 and P=0.00, respectively). The increases of endometrial thickness suggested no statistically significant difference between the two treatment groups. The G-CSF with TEAS group suggested a higher embryo implantation rate than the G-CSF perfusion only and control groups (33.33% & 29.1% and 33.33% & 17.39%; P=0.412 and 0.091, respectively). The G-CSF combined with TEAS group demonstrated nominally higher clinical and ongoing pregnancy rates than the G-CSF perfusion only group and controls, though the difference was not statistically significant. Conclusions: G-CSF has a potential role in improving endometrium thickness in patients with thin unresponsive endometrium in FET treatment cycles. Besides, when combined with TEAS, G-CSF perfusion treatment also improves the embryo implantation rate. G-CSF perfusion combined TEAS treatment during FET cycles is a preferable choice for patients with thin endometrium.